The Influences of Human-Made Disasters on the State of Government to Citizens ICT Services: Users’ Perspectives - Abdulrahman, Saifuldeen H.; Kamaruddin, Siti Sakira; Othman, Nafishah Bt; Abdulrahman, Mohammad S. (International Journal of Advanced Science and Technology, 2019)
The recent human-made disasters in middle-east harmed the governments’ functionality which caused difficulties on various aspects of life for citizens. These affected governments' functions include government to citizens (G2C) ICT services. There is an absence of empirical study to clarify the real situation of the government to citizens ICT services among citizens during a human-made disaster. Where government to citizens ICT services could fit and serve the affected people due to the difficulties and risks that hinder their access to the government sites. This paper attempts to fill this gap in the literature by empirically investigating these services in Iraq as a war-torn country. In this paper, the literature review has been conducted; the investigated issue is recognised by conducting a self-administered survey. Results point out that there is a lack of flexibility when using ICT services, and there is a notable ignorance about the availability of G2C ICT services among IDPs.